PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL MELALUI PERMAINAN TRADISIONAL TARIK UPIH DALAM MENINGKATKAN MOTORIK KASAR ANAK - Ajriah Muazimah; Ida Windi Wahyuni (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Character education is the foundation of children for their future and character education serves as the basis for self-discipline and becomes a means of controlling children when they behave. Values ​​that are not necessarily by the surrounding community. Noble values ​​can be sourced from existing local wisdom, wisdom values ​​to realize the aspirations of the nation physically and mentally. Through traditional games, it is also a form of tradition in people's lives to create an atmosphere and expression that is fun and uplifting to build children's character from an early age. Traditional games that can be categorized as good must be able to help aspects of children's development both physically and psychologically. Traditional games of attraction are sufficient to explore the physical abilities of children. When playing the game of attraction, children interact a lot with others, control emotions, cooperate, respect friends, and hone language skills. Introducing local wisdom through traditional games of Tarik-upih to children from an early age will form a person who cares and has a love for their culture. So that there will be generations with personalities and functional values ​​for the nation and state.